Microwave-assisted synthesis of imprinted polymer for selective removal of arsenic from drinking water by applying Taguchi statistical method. (December 2018) - Mustafai, Faraz Ahmed; Balouch, Aamna; Abdullah,; Jalbani, Nusrat; Bhanger, Muhammad Iqbal; Jagirani, Muhammad Saqaf; Kumar, Ameet; Tunio, Aqsa
Graphical abstract: Highlights: Arsenic imprinted polymer synthesized for the detoxification drinking water. 1-Vinylimidazole and methacrylic acid were to synthesize arsenic imprinted polymer. Synthesized imprinted polymer has excellent selectivity for arsenic then other competitive ion. Taguchi method was applied to optimize the process parameters for adsorption of arsenic on As-IIP. Abstract: In the present study, As 3+ imprinted polymer as an active detoxification material has been synthesized through microwave assisted preparation method. By inducing the microwave radiation during the polymerization process decreases the reaction time to about 10 folds than conventional method. The imprinted polymer is one of the best possible techniques for the removal of arsenic, and various other contaminants from drinking water. The SEM and FTIR analyses have been conducted to clarify microstructure, surface morphology and size distribution of the synthesized imprinted polymer. The main parameters affecting the pzc, pH, agitation time, shaking speed, concentration, the temperature of adsorbent and percent of sorption, have been examined and optimized by Taguchi design. Taguchi L9 orthogonal array was employed to optimize the important factors versus % sorption values with nine experimental runs at 3 levels. Moreover, to understand the reaction phenomenon Langmuir and Freundlich isotherms, kinetic models and thermodynamics of adsorption process were calculated. The relative selectivity coefficient of imprinted polymer for As 3+ /Cd 2, As 3+ /Zn 2+, As 3+ /Ni 2+ were respectively 45.93, 131.01, 262.63 times greater than for non-imprinted polymer. The limit of detections (LOD) and limit of quantification (LOQ) of the proposed procedure for As 3+ ion was found to be 1.0 µg/L and 3.3 µg/L for the As 3+ ion respectively, with the relative standard deviation (RSD) of 4%. The excellent adsorption performance along with their low cost and convenient synthesis makes this range of adsorbent highly promising for commercial applications in drinking water purification and water treatment.